2013
DOI: 10.1038/gene.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Induction of murine adenosine A2A receptor expression by LPS: analysis of the 5′ upstream promoter

Abstract: Non-activated macrophages express low levels of A(2A)Rs and lipopolysaccharides (LPS) upregulates A(2A)R expression in an NF-κB-dependent manner. The murine A(2A)R gene is encoded by three exons, m1, m2 and m3. Exons m2 and m3 are conserved, while m1 encodes the 5' untranslated UTR. Three m1 variants have been defined, m1A, m1B and m1C, with m1C being farthest from the transcriptional start site. LPS upregulates A(2A)Rs in primary murine peritoneal and bone-marrow-derived macrophages and RAW264.7 cells by sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This change was not surprising as, in prior studies, we and others had demonstrated that there is upregulation of both A2AR receptor expression and function following exposure to inflammatory stimuli (IL-1β and tumour necrosis factor (TNF)) which acts as a feedback regulator of inflammation in both murine and human cells323334353637. One explanation for the difference between A2AR expression in human and murine OA cartilage is that the findings in A2AR KO mice do not reflect OA development in humans.…”
Section: Resultsmentioning
confidence: 72%
“…This change was not surprising as, in prior studies, we and others had demonstrated that there is upregulation of both A2AR receptor expression and function following exposure to inflammatory stimuli (IL-1β and tumour necrosis factor (TNF)) which acts as a feedback regulator of inflammation in both murine and human cells323334353637. One explanation for the difference between A2AR expression in human and murine OA cartilage is that the findings in A2AR KO mice do not reflect OA development in humans.…”
Section: Resultsmentioning
confidence: 72%
“…Increased activity of CD73 (5=-ectonucleotidase), the main regulator of adenosine metabolism, has been documented in exercising rats (38). We and others have shown that adenosine receptor expression can rapidly be increased in the presence of adenosine itself or stress induced by the addition of lipopolysaccharide (16,17,53,76,80). This is the first report showing that adenosine receptors are upregulated by continuous exercise.…”
Section: Adenosine Receptors Are Upregulated By Exercise: a Potentialmentioning
confidence: 70%
“…Previous studies have shown the up-regulation of A 2A Rs in macrophages activated by LPS stimulation [1619]. This up-regulation is believed to sensitize macrophages to adenosine signaling by priming M1 macrophages to respond to adenosine and thus switching toward the M2d phenotype.…”
Section: Resultsmentioning
confidence: 96%